Expression of intrahepatic CD3, CD4, and CD8 T cells in biliary atresia - Behairy, Behairy E.; Ehsan, Nermine; Anwer, Magdy; Allam, Alif; El-Henawy, Ibramem; Hameed, Nesreen Abdel; Zakaria, Haidy M. (Clinical and Experimental Hepatology, 2018)
Aim of the study : Assessment of the expression of cluster of differentiation (CD)3, CD4, and CD8 T cells in biliary atresia (BA) cases in comparison to neonatal cholestasis other than BA. Material and methods : This study included 79 patients: 34 patients with BA (BA group) and 35 patients with neonatal cholestasis due to causes other than BA (cholestasis group), and 10 normal liver donor as a control group. Immunohistochemical staining or CD3, CD4, and CD8 T cells in liver tissues for the 3 groups were evaluated. Results : Presence of clay stool, high gamma-glutamyl transferase levels, thrombocytosis, and non-contractibility of the gallbladder was the main clinical, laboratory, and radiological findings, distinguishing BA from other disorders causing neonatal cholestasis. Portal ductular proliferation, bile plugs in portal ductules, and advanced grades of fibrosis were more predominant in liver biopsy specimens of BA patients. The CD3+, CD4+, and CD8+ expression in patients with BA were significantly higher than in both cholestasis and control groups, while it was comparable in the cholestasis and control groups, with cutoff values of 25, 12, and 2.5 cells/portal tract, respectively, differentiating between BA and cholestatic patients. Conclusions : Immune-mediated destruction of bile ducts is incriminated in the pathogenesis of BA. Lymphocytic infiltrate in portal tract is primarily composed of CD3, CD4, and CD8 T cells. Immunostaining of liver tissue for CD3, CD4, and CD8 T cells can help in ensuring diagnosis of BA.